Palladium bis-pincer complexes with controlled rigidity and inter-metal distance. Issue 22 (7th October 2020) - Yu, Cheng-Han; Zhu, Congzhi; Ji, Xiaozhou; Hu, Wei; Xie, Haomiao; Bhuvanesh, Nattamai; Fang, Lei; Ozerov, Oleg V.
Abstract : We report a series of redox-active bis(pincer) Pd(ii ) complexes in which the redox active units are based on either a diarylamido or a carbazolide framework. Abstract : We report a series of redox-active bis(pincer) Pd(ii ) complexes in which the redox active units are based on either a diarylamido or a carbazolide framework. Compounds 1 and 2 contain two full diarylamido/bis(pincer) PNP units connected either via an Ar–O–Ar linker (1 ) or an Ar–Ar bond (2 ). Compound 3 is a fused bis(pincer) where the two PNP units share an aromatic ring. Compound 4 is built around an indolo[3, 2- b ]carbazole core in which two NNN pincers share an aromatic ring similarly to 3 . These metal complexes all display two reversible oxidation waves with the Δ E values increasing in the order of 1 < 2 < 4 < 3 . The same trend in increasing electronic coupling emerges from the analysis of the IV-CT bands in the NIR portion of the optical spectra. The analysis of these compounds was further advanced by data from EPR spectroscopy, X-ray diffractometry, and DFT calculations. It is concluded that the monooxidized cations 2 + –4 + belong to Class III on the Robin-Day classification of mixed-valence compounds. Compound 4 possesses enforced near-planarity that enables delocalization of the unpaired electron in 4 + across a broader conjugated system compared to 3 + .